2022
DOI: 10.1097/j.jcrs.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of astigmatism correction using femtosecond laser combined with cataract surgery: penetrating vs intrastromal incisions

Abstract: To compare the effectiveness of penetrating vs intrastromal femtosecond laser corneal relaxing incisions (CRIs) in reducing corneal astigmatism during cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…4 In femtosecond laser-assisted cataract surgery combined with penetrating and intrastromal corneal relaxing incisions, multiple regression analyses revealed that longer corneal relaxing incision length, higher preoperative corneal astigmatism magnitude, and ATR corneal astigmatism produced greater net corneal changes. 14 In this study, no correlation between the net refractive changes and incision length was found when a single PCRI was made, whereas refractive changes and incision length were correlated with paired incisions, but with a small correlation coefficient. This discrepancy may be explained by 2 factors: (1) In this study, PCRIs were used to reduce the residual manifest refractive astigmatism; in contrast, previous studies noted above used PCRIs to reduce corneal astigmatism; and (2) in this study, sample size and range of incision length were small (32 to 45 degrees) in the single PCRI group.…”
Section: Discussioncontrasting
confidence: 57%
“…4 In femtosecond laser-assisted cataract surgery combined with penetrating and intrastromal corneal relaxing incisions, multiple regression analyses revealed that longer corneal relaxing incision length, higher preoperative corneal astigmatism magnitude, and ATR corneal astigmatism produced greater net corneal changes. 14 In this study, no correlation between the net refractive changes and incision length was found when a single PCRI was made, whereas refractive changes and incision length were correlated with paired incisions, but with a small correlation coefficient. This discrepancy may be explained by 2 factors: (1) In this study, PCRIs were used to reduce the residual manifest refractive astigmatism; in contrast, previous studies noted above used PCRIs to reduce corneal astigmatism; and (2) in this study, sample size and range of incision length were small (32 to 45 degrees) in the single PCRI group.…”
Section: Discussioncontrasting
confidence: 57%
“…Similar to our study, AK with FLACS, anterior penetrating and intrastromal, found greater astigmatic changes in patients with preoperative ATR astigmatism. 30 The major limitations of our study are that it is retrospective, and a well-established nomogram to calculate manual LRIs using ACA data was arbitrarily modified to calculate the parameters for femtosecond AKs. Our modification is similar to a published nomogram comparing LRI versus femtosecond AK, side by side.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, AK with FLACS, anterior penetrating and intrastromal, found greater astigmatic changes in patients with preoperative ATR astigmatism. 30…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ganesh et al[ 81 ] in a randomized clinical trial, demonstrated that although anterior penetrating and iAK incisions were effective in reducing preoperative astigmatism using the FLS, the transepithelial approach showed comparatively better correction. Recently, Wang et al [ 76 ] in another large-sample randomized clinical trial demonstrated comparable outcomes.…”
Section: Astigmatism Correction With Corneal Incisionsmentioning
confidence: 99%